Electrohydrodynamic atomization deposition and mechanical polishing of PZT thick films. Issue 11 (15th August 2016) - Wang, D.; Li, X.; Shi, P.; Zhao, X.; Liang, J.; Ren, T.; Dong, W.; Yang, R.; Wang, Y.; Dorey, R.A.
Abstract: In this work, electrohydrodynamic atomization deposition, combined with mechanical polishing, was used for the fabrication of dense and even PZT thick films. The PZT slurry was ball-milled and the effect of milling time on the characteristics of the deposited films was examined. A time of 50 h was found to be the optimum milling time to produce dense films. It was found that the PZT thick films presented rough surface after deposition. In order to overcome this drawback the mechanical polishing process was employed on the deposited films. After the mechanical polishing the roughness (Ra) and peak-to-peak height (Rz) of the film surface were decreased from 422 nm to 23 nm and from 5 µm to 150 nm, respectively. Subsequently, an increase of 10 pC N −1 on piezoelectric constant (d33, f ) was obtained. In addition, it was observed that the d33 was increased from 57 pC N −1 to 89 pC N −1 when the thickness was increased from 10 µm to 80 µm.